Critical Analysis of Leadership Strategies, Hospital Efficiency, And Patient-Centered Care Models - Saq, Hassan Mana Ali Abu; saq, Jaber Ali Jaber Ali Abu; Asiri, Salihah Mohammed Ahmed; Alsharyah, Saleh Mahdi Hamad; Alsalem, Ali Hamad Naser; H, Alyami, Mohammed Dawas; Alyaqoob, Wardah Saeed M; Almansour, Dawas Mohammed H; Almansour, Ali Fahad S; Alshahrani, Fathiyyah Amer Mohammed (Journal of Ecohumanism, 2024)
The healthcare industry is still developing; the directional trends have started to lean towards better hospital management strategies that would result in better patient care. In this paper, I critically review different leadership approaches in hospital contexts with success in organizational effectiveness and patient care delivery systems. Issues like leadership styles, including transformational, transactional, and servant leadership, logistical factors and clinical implications, and patient satisfaction are discussed on the operational level. Qualitative interviews are conducted Using qualitative and quantitative study methods, with results being statistically compared with corresponding quantitative hospital variables such as patient satisfaction, staff turnover, and readmission rates. The research indicates that the study has provided recommendations showing that Michigan Organizational QL is essentially predictive of cross-functional team collaboration and can be used to predict patient-centered care models. Finally, the paper contemplates the best recommendations that healthcare administrators and policymakers should consider embracing in order to raise standards in the direction, quality, and productivity of hospitals and care outcomes through purposes that embrace patient-centered care.